The recipients of Polish, Greek and Cypriot legal norms. Linguistic exponents - Gortych-Michalak, Karolina (My University, 2014)
The paper is dedicated to highlighting and indicating linguistic exponents used for needs to express the recipients of legal rules, which are present in Polish, Greek and Cypriot normative acts. The thesis of the investigation is the suspicion of designation or denotation or different relations existing between linguistic exponents referring to the recipients of legal rules and the real recipients of legal rules. Before the empirical investigations are conducted, some characteristics of legal language (statutory language) are given. The statutory language is understood as the language used express and to formulate legal rules. Thus, language of legal rules is an abstract creation as it is the interpreted form of the statutory language. Then a typical legal rule might be seen as an utterance saying: “X (in the circumstances Y) does Z”. The statutory language has a specific character and function, which is to express and to verbalize legal rules, thus considering the typology of legal rules, which is division into general legal rules(lex generalis) and specific legal rules (lex specialis), the linguistic exponents of these rules are presented. They are derived from Polish, Greek and Cypriot normative acts, more specifically, they form the laws. The next step of the investigation is to present the linguistic exponents used to specify the recipients of legal rules. The presentation is based on the relations of designation or denotation or different and the analysed linguistic exponents are given in confrontational aspect. The summaries and conclusions of the whole investigation are discussed in the final remarks of the paper. The final step of the investigation is to propose where and how the results of the performed investigations might be used as the applied linguistic, legal translatology especially seems the appropriate applicable field. Keywords: legal language, language of the law, language of legislation, comparative analysis of legal languages, legal clauses, legal norms, legal rules, linguistic phenomena of the law
ΠΑΡΑΛΗΠΤΕΣ ΤΩΝ ΠΟΛΩΝΙΚΩΝ, ΕΛΛΗΝΙΚΩΝ ΚΑΙ ΚΥΠΡΙΑΚΩΝ ΚΑΝΟΝΩΝ ΔΙΚΑΙΟΥ. ΓΛΩΣΣΙΚΟΙ ΕΚΘΕΤΕΣ
ODBIORCY PRAW POLSKICH, GRECKICH I CYPRYJSKICH. WYKŁADNIKI JĘZYKOWE
Keywords: legal language; language of the law; language of legislation; comparative analysis of legal languages; legal clauses; legal norms; legal rules; linguistic phenomena of the law